Simulation of GIMT's FMS for precision machining - Yim, Simon Kok Meng. (2009)
In this research project, computer simulation using SLAM II was performed on GIMT's precision machining FMS (Flexible Manufacturing System). Simulation was used as a tool to study the resource requirements in FMS for the manufacture of two part types. Animation graphics was also used as a visual means of verifying the model.